Evangelische Pfarrhäuser in Bayern - Hübner, Hans-Peter; May, Herbert; Raschzok, Klaus; Hagen, Gerhard (Franz Schiermeier Verlag, 2017)
Der Band enthält die Pfarrhäuser in Nürnberg, Markt Erlbach, Roßtal, Holzschwang, Eschenau, Leipheim an der Donau, Schauenstein, Betzenstein, Bieswang, Zell, Hohenaltheim, Pfuhl, Schwimbach, Obernsees, Großgründlach, Gutenstetten, Ostheim vor der Rhön, Fessenheim, Gärtenroth, Bruck, Dietenhofen, Ipsheim, Beerbach, Pommersfelden, Joditz, Bürglein, Unterschwaningen, Burghaslach, Neudrossenfeld, Ortenburg, Großkarolinenfeld, Castell, Marktredwitz, Kleinsorheim, Küps, Bad Kissingen, Selb, Forchheim, Neuses, Merkendorf, Vohenstrauß, Dittenheim, Perlach, Laubendorf, Grosselfingen, Füssen, Heidingsfeld, Partenkirchen, Karlshuld, Eltersdorf, Eschenbach, Lonnerstadt, Landshut, Schweinfurt, Dachau, Hirschegg, Straubing, Lindau, Inzell, Burgpreppach, Memmingen, Marktbergel und Alerheim.